(+)-α-copaen-8-one and other constituents from Neomirandea species - Tamayo Castillo, Giselle (1989)
The investigation of five Neomirandea species gave two known entclerodanes, a heliangolide, a cadinene and a new copaene derivative as well as some widespread compounds.